2014
DOI: 10.1186/2251-6581-13-64
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of broccoli sprouts powder and standard triple therapy on cardiovascular risk factors following H.pylori eradication: a randomized clinical trial in patients with type 2 diabetes

Abstract: BackgroundIn this clinical trial we compared the effects of broccoli sprouts powder, as an alternative and complementary treatment, to those of standard triple therapy, as a common medical treatment, on cardiovascular risk factors following the H.pylori eradication in patients with type 2 diabetes.MethodsEighty-six type 2 diabetic patients with positive H.pylori stool antigen test (HpSAg) were randomized to receive one of the three following regimens: STT) Standard triple therapy (omeprazole 20 mg, clarithromy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 39 publications
(36 reference statements)
4
37
0
Order By: Relevance
“…In addition, due to its antioxidant and anti-inflammatory properties, it has a beneficial effect on the cardiovascular system, which has been confirmed by both in vitro and animal studies. Mirmiran et al [ 77 ] have shown that broccoli extract and other products with a high GR content reduce the plasma low-density lipoprotein (LDL) cholesterol, but the mechanism of this interaction is not yet known.…”
Section: Plant-derived Sulfur Compounds—gsls and Oscsmentioning
confidence: 99%
“…In addition, due to its antioxidant and anti-inflammatory properties, it has a beneficial effect on the cardiovascular system, which has been confirmed by both in vitro and animal studies. Mirmiran et al [ 77 ] have shown that broccoli extract and other products with a high GR content reduce the plasma low-density lipoprotein (LDL) cholesterol, but the mechanism of this interaction is not yet known.…”
Section: Plant-derived Sulfur Compounds—gsls and Oscsmentioning
confidence: 99%
“…Cardiovascular disease risk in Helicobacter pylori -infected T2D patients was shown to be reduced after administration of broccoli sprouts powder [75]. However, in 40 hypertension patients consuming 10 g of dried broccoli sprouts for 4 weeks, no changes in blood pressure or flow mediated dilation were detected [76].…”
Section: Clinical Trials With Disease-related Outcomes Using Isothiomentioning
confidence: 99%
“…In 2015, a study showed that a broccoli diet containing high levels of GR reduced plasma LDL cholesterol levels significantly . Cardiovascular disease risk in H. pylori ‐infected T2D patients was shown to be reduced after administration of broccoli sprouts powder . However, in 40 hypertension patients consuming 10 g of dried broccoli sprouts for 4 weeks, no changes in blood pressure or flow‐mediated dilation were detected .…”
Section: Clinical Trials With Disease‐related Outcomes Using Isothiomentioning
confidence: 99%
“…The preventing effect of sinigrin may be due to the ability to suppress the production of inflammatory cytokines and the expression of pro-atherogenic factors in serum, aorta, and liver tissue [inhibits the VCAM-1 expression via preventing NF-κB and p38 MAPK/JNK pathways in MOVAS cells] [7]. Clinical trials that have used isothiocyanate supplementation by increasing food consumption with high concentration of these compounds, shown a decrease in LDL levels and an improvement in blood pressure control [152,153]. Recently, in a rabbit model of cardiac failure, the supplementation with Sulforaphane [0.5 mg/kg in a subcutaneous dose for five days per twelve-week] improved ventricular cardiac function and remodeling by inhibiting oxidative stress and inflammation with a possible mitochondrial role [154].…”
Section: Bioactive Compounds With Mitochondrial Protective Functionmentioning
confidence: 99%